1993
DOI: 10.1016/0168-1591(93)90030-s
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and behavioral effects of handling and restraint in the ball python (Python regius) and the blue-tongued skink (Tiliqua scincoides)

Abstract: Reptiles are handled during transport, veterinary care, education programs, and as companion animals. This study investigated corticosterone levels (CS), heterophil/lymphocyte ratio (H/L), and behavioral responses to routine handling in the ball python (Python regius) (n=4) and the blue-tongued skink (Tiliqua scincoides) (n=3). We validated the RSL I 1~ Corticosterone Kit for rodents for parallelism and recovery, and found this to be a precise and highly specific means of CS measurement in reptiles. To determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 26 publications
1
16
1
Order By: Relevance
“…Handling of reptiles is an important trigger for increases in both corticosterone and adrenal catecholamines (Lance and Lauren, 1984;Grassman et al, 1992;Kreger and Mench, 1993). In free-ranging animals, restraint is usually associated with consumption by a predator thus handling may elicit a fight or flight response (DeNardo, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Handling of reptiles is an important trigger for increases in both corticosterone and adrenal catecholamines (Lance and Lauren, 1984;Grassman et al, 1992;Kreger and Mench, 1993). In free-ranging animals, restraint is usually associated with consumption by a predator thus handling may elicit a fight or flight response (DeNardo, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our working definition of stress is 'the physiological response of an animal to an experimental stimulus, as measured by elevated circulating glucocorticoid levels'. Changes in plasma corticosterone levels have been used to assess the impact of capture, handling, restraint and confinement on reptilian species (Moore et al, 1991;Cree et al, 2003;Cree et al, 2000;Mathies et al, 2001;Kreger and Mench, 1993;Cash et al, 1997), but the amount of stress induced by alternative commonly used research procedures beyond initial capture and housing has not been previously assessed. The present paper describes a study that set out to quantify the ways in which plasma corticosterone levels in lizards are affected by a variety of methods that are commonly used in fields of research such as behavioural ecology and microevolution.…”
Section: Introductionmentioning
confidence: 99%
“…However, numerous scientific and other reports emphasise that snakes, including more sedentary species such as the Ball python, require the ability to fully straighten their bodies to satisfy their need for behavioural normality, exercise, avoidance of stress and disease, alleviation of physical discomfort, and achievement of physical comfort [26,29,[37][38][39] For example, Kreger and Mench [40] found that Ball pythons that were restrained in a container prior to handling demonstrated a significant rise in plasma corticosterone (CS) levels, potentially indicating an acute stress response. Given that the majority of the snakes observed during our study were not given the ability to extend their bodies to full and unrestricted natural length, it is arguable that the current husbandry practices could likely be having a negative impact on the welfare of the Ball pythons that are housed in this manner.…”
Section: Mobilitymentioning
confidence: 99%